Electrolyte infiltration degree detection method and application thereof

By adding fluorescent agent to the electrolyte of lithium-ion batteries, disassembly and detecting before the battery cell is pre-charged and pre-charged, the fluorescence distribution of ultraviolet light is used to solve the problem that the degree of infiltration of the electrolyte in the battery is difficult to accurately detect, and the improvement of battery circulation performance and safety is achieved.

CN119845804APending Publication Date: 2025-04-18EVE ENERGY CO LTD

Patent Information

Application Number
CN202411759223.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to accurately and quickly detect the degree of infiltration of electrolyte in lithium-ion batteries, affecting the cycling performance and safety of the battery.

Method used

By adding a fluorescent agent to the electrolyte and disassembling the cell before the cell is pre-filled into, the fluorescence distribution in the cell assembly is detected by ultraviolet light irradiation, and the degree of infiltration of the electrolyte is qualitatively or quantitatively.

Benefits of technology

This method can more intuitively and quickly judge the infiltration of the electrolyte, reduce errors, optimize the electrolyte injection and static parameters, and improve the circulation performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845804A_ABST
    Figure CN119845804A_ABST
Patent Text Reader

Abstract

The invention provides a method for detecting the infiltration degree of an electrolyte, which comprises the following steps: S1, injecting an electrolyte containing a fluorescent agent into a battery cell, standing, and disassembling the battery cell; and S2, ultraviolet light is adopted to irradiate the battery cell assembly obtained by disassembling the battery cell, the battery cell assembly comprises at least one of a positive plate, a negative electrode and a diaphragm, and the infiltration degree of the electrolyte is judged according to the fluorescence distribution condition. According to the method for detecting the infiltration degree of the electrolyte, the infiltration degree of the electrolyte on the positive plate, the negative electrode or the diaphragm can be qualitatively or quantitatively judged by detecting the fluorescence distribution condition of the positive plate, the negative electrode or the diaphragm, so that electrolyte injection and standing parameters are further optimized, and the rate capability, the cycle performance and the safety of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for detecting electrolyte infiltration degree and application thereof. Background Art

[0002] Lithium-ion batteries have high specific energy density and capacity retention, and are gradually being widely used in the field of vehicle power. As consumers' requirements for the endurance and safety of electric vehicles increase, the energy density and safety standards of electric vehicle batteries have also been greatly improved. Therefore, researchers in this industry have continuously increased the requirements for the coating surface density and compaction of the positive and negative electrodes, and continuously reduced the electrolyte retention volume. Although these measures can effectively improve the energy density of the battery, they will cause the electrolyte infiltration distance to be lengthened and the infiltration speed to be slowed down, which is not conducive to the infiltration of the electrolyte and affects the subsequent long-term performance of the battery.

[0003] The degree of electrolyte wetting is affected by the injection process, static process and other conditions, but the optimal parameters of the injection process and static process are difficult to explore and require a lot of experimental verification. Therefore, when optimizing the electrolyte injection, static parameters and conditions, it is necessary to have an accurate and fast method to understand the distribution of the electrolyte in the battery in order to maximize the battery cycle performance and safety. At present, there are mainly the following methods to observe the electrolyte wetting condition inside lithium-ion cylindrical batteries:

[0004] (1) By observing the dry area of ​​the diaphragm, this method can only characterize the infiltration at the macro level, and the microscopic detection accuracy is poor.

[0005] (2) Whether the fully charged interface is fully charged after formation can be observed to determine whether the infiltration is sufficient. If the infiltration is insufficient, the transmission of electrons and ions will be blocked, and the negative electrode will not be embedded with lithium or will not be fully embedded with lithium, so it will show brown or purple dark spots. However, the fully charged interface is not only related to the electrolyte infiltration, but also to many factors such as the film formation and the wavy edge of the electrode. Therefore, the fully charged interface will be affected by many factors, and it is difficult to intuitively observe the infiltration of the electrolyte inside the battery cell, so it is quite limited.

[0006] (3) The P element content in each area of ​​the electrode surface is detected using an energy dispersive spectrometer (EDS) to characterize the degree of electrolyte infiltration. However, this method is limited by the test accuracy and therefore has a large detection error.

[0007] (4) By testing the battery cycle performance and capacity retention rate, determine whether the electrolyte is fully infiltrated. Insufficient electrolyte penetration will limit the diffusion range of lithium ions, resulting in uneven distribution of lithium ions during the battery charge and discharge process, which ultimately manifests as a decrease in battery capacity and deterioration in cycle performance. However, since there are too many factors affecting cycle performance, it is difficult to accurately optimize the conditions of the battery injection process and static process. Summary of the invention

[0008] The purpose of the present invention is to provide a method for detecting the degree of electrolyte infiltration and its application. The method for detecting the degree of electrolyte infiltration can qualitatively or quantitatively judge the degree of electrolyte infiltration in the positive electrode sheet, the negative electrode or the diaphragm by detecting the fluorescence distribution of the positive electrode sheet, the negative electrode or the diaphragm, thereby further optimizing the electrolyte injection and static parameters and improving the cycle performance and safety of the battery.

[0009] According to one aspect of the present invention, there is provided a method for detecting the degree of electrolyte infiltration, comprising the following operations: S1. injecting a battery cell with an electrolyte containing a fluorescent agent, letting the battery cell stand, and then disassembling the battery cell; S2. irradiating a battery cell assembly obtained by disassembling the battery cell with ultraviolet light, wherein the battery cell assembly comprises at least one of a positive electrode sheet, a negative electrode, and a diaphragm, and judging the degree of electrolyte infiltration according to the fluorescence distribution.

[0010] By injecting an electrolyte containing a fluorescent agent into the battery cell, disassembling the battery cell before pre-charging and forming the battery cell, and irradiating the battery cell assembly with ultraviolet light, the area in the battery cell assembly that is infiltrated with the electrolyte containing the fluorescent agent produces a fluorescent effect. Thus, by detecting the fluorescence distribution of the positive electrode sheet, the negative electrode or the diaphragm, the degree of electrolyte infiltration in the positive electrode sheet, the negative electrode or the diaphragm can be qualitatively or quantitatively determined. If the fluorescence distribution is uniform, it means that the battery cell assembly has been completely infiltrated by the electrolyte, which will be beneficial to the stability and safety of the battery during the charge and discharge process. On the contrary, if there is an area in the battery assembly where the fluorescence effect cannot occur, it means that the electrolyte infiltration of the battery cell assembly is insufficient, which will not only reduce the ion conduction efficiency and active material utilization rate of the battery cell, but also increase thermal runaway and safety risks. It should be noted here that the pre-charging and forming operation of the battery involves many chemical reactions. In the battery after pre-charging and forming, the infiltration of the electrolyte will be affected by many factors, and it is difficult to intuitively observe the infiltration of the electrolyte inside the battery cell. This solution detects the infiltration of the electrolyte before the pre-charging of the battery cell. Since it does not involve chemical reactions, it can reduce errors, thereby more intuitively and efficiently judging the infiltration of the electrolyte on the positive electrode, negative electrode or diaphragm.

[0011] Preferably, the fluorescent agent includes a phthalimide fluorescent agent. The phthalimide fluorescent agent has good solubility in the electrolyte. By using the phthalimide fluorescent agent, the influence of the fluorescent agent on the physical properties of the electrolyte can be reduced, so that the surface tension of the electrolyte before and after the introduction of the fluorescent agent is similar, thereby the error measured by the detection method of the electrolyte infiltration degree is smaller.

[0012] Preferably, the concentration of the fluorescent agent in the electrolyte is 0.1 to 3.2 wt %. By adjusting the concentration of the fluorescent agent in the electrolyte to the above range, the electrolyte containing the fluorescent agent can produce a fluorescent effect under ultraviolet light, and the effect of the fluorescent agent on the wetting characteristics of the electrolyte can be reduced. The contact angle of the electrolyte with the fluorescent agent introduced to the positive electrode sheet, the negative electrode or the diaphragm is similar to the contact angle of the electrolyte without the fluorescent agent introduced to the positive electrode sheet, the negative electrode or the diaphragm, which can better simulate the degree of wetting of the electrolyte.

[0013] Preferably, the content of the fluorescent agent in the electrolyte is 0.1-0.8 wt %.

[0014] Preferably, the content of the fluorescent agent in the electrolyte is 0.1-0.4 wt %.

[0015] Preferably, the content of the fluorescent agent in the electrolyte is 0.2wt%. By adjusting the amount of the fluorescent agent added, the concentration of the fluorescent agent in the electrolyte containing the fluorescent agent is 0.2wt%, which can not only make the electrolyte produce an obvious fluorescent effect and reduce the difficulty of detecting the fluorescence distribution, but also reduce the influence of the fluorescent agent on the wetting characteristics of the electrolyte, thereby reducing the system detection error of the detection method of the electrolyte wetting degree.

[0016] Preferably, the electrolyte includes at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate. The method for detecting the degree of electrolyte wetting is applicable to an electrolyte system using at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate as a solvent.

[0017] Preferably, the electrolyte includes dimethyl carbonate. When the electrolyte includes dimethyl carbonate, the physical properties of the electrolyte system can be regulated, so that after the fluorescent agent is added to the electrolyte, the influence of the physical properties of the electrolyte is more controllable, the change trend of the contact angle is more stable, and the electrolyte system has a smaller degree of interference with the fluorescence effect, which can further reduce the detection error of the detection method of the electrolyte infiltration degree.

[0018] Preferably, the content of dimethyl carbonate in the electrolyte is not less than 50 wt %.

[0019] Preferably, the electrolyte includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).

[0020] Preferably, the electrolyte further includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiODFB), 1,3-propanesultone (PS), and fluoroethylene carbonate (FEC).

[0021] Preferably, the total content of lithium hexafluorophosphate, bis(fluorosulfonyl)imide lithium salt and lithium difluorooxalatoborate in the electrolyte is not higher than 20 wt %.

[0022] Preferably, the electrolyte includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide salt and lithium difluorooxalatoborate.

[0023] Preferably, the total content of 1,3-propane sultone and fluoroethylene carbonate in the electrolyte is not higher than 5 wt %.

[0024] Preferably, the electrolyte includes 1,3-propane sultone and fluoroethylene carbonate.

[0025] Preferably, the area where the battery cell assembly produces a fluorescent effect is represented by a fluorescent area, and the area where the battery cell assembly does not produce a fluorescent effect is represented by a non-fluorescent area; the standard for determining the degree of electrolyte infiltration is: the fluorescent area is an area with good electrolyte infiltration, and the non-fluorescent area is an area without electrolyte infiltration.

[0026] Preferably, the battery cell is a cylindrical battery cell, and the area where the battery cell assembly does not produce a fluorescent effect is represented by a non-fluorescent area; when judging the degree of infiltration of the electrolyte, the degree of infiltration of the electrolyte in the battery cell assembly is judged according to the width of the non-fluorescent area. During the detection process, it was found that the distribution law of the electrolyte in the cylindrical battery cell is as follows: in the width direction of the electrode piece, the fluorescence signal intensity at both ends of the battery cell assembly is high, the fluorescence signal intensity in the middle of the battery cell assembly is low, and the fluorescence signal intensity from both ends to the middle of the battery cell assembly presents a gradient distribution. This is because when the cylindrical battery cell is injected, after the electrolyte enters the bottom of the shell from the center hole position of the winding core, the electrolyte gradually flows and penetrates from the positive and negative ends to the middle position. Therefore, the electrolyte infiltration in the area of ​​the winding core of the battery cell assembly close to the center hole and the area at the end of the winding core is faster, and the electrolyte infiltration in the middle area of ​​the battery cell assembly is slower. Therefore, the degree of infiltration of the electrolyte in the battery cell assembly can be judged by measuring the width of the non-fluorescent area.

[0027] Preferably, when judging the degree of electrolyte infiltration, the following operations are included: dividing the battery cell assembly into M parts in the length direction and dividing the battery cell assembly into N parts in the width direction, so that the battery cell assembly is divided into M*N regions, M≥2, N≥2; testing the fluorescence intensity of the M*N regions respectively, and normalizing the fluorescence intensity of the M*N regions to quantitatively characterize the degree of electrolyte infiltration in the battery cell assembly. By dividing the positive electrode sheet, negative electrode or diaphragm into M*N regions, and testing the fluorescence intensity of each region respectively, and normalizing the fluorescence intensity of different regions, the electrolyte infiltration path can be determined, thereby optimizing the corresponding infiltration method according to the electrolyte infiltration path of different batteries.

[0028] Preferably, M=3, N=3.

[0029] Preferably, an X-ray fluorescence spectrometer is used to perform the fluorescence intensity test.

[0030] According to another aspect of the present invention, the application of the above-mentioned electrolyte wetting degree detection method in optimizing the design of lithium-ion batteries is provided. By adopting the electrolyte wetting degree detection method, the electrolyte wetting route can be detected more intuitively, which is conducive to finding the key factors affecting battery wetting. Therefore, by using the electrolyte wetting degree detection method, the battery's injection, static and other process parameters can be optimized, and the injection and wetting conditions that have a greater impact on the wettability can be explored.

[0031] Preferably, the lithium-ion battery includes a soft-pack battery, a cylindrical battery, or a square battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The fluorescence effect of the diaphragm, positive electrode and negative electrode measured in Example 3;

[0033] Figure 2 Schematic diagram of the division method of the separator, the positive electrode sheet and the negative electrode in Example 4;

[0034] Figure 3 A schematic diagram of the cycle capacity retention rate of the batteries provided for the experimental groups 5-1B to 5-3B; Figure 4 This is the fluorescence effect of the negative electrode measured in Example 2. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0036] Example 1

[0037] (1) Preparation of electrolytes with different fluorescent agent concentrations

[0038] In this embodiment, the experimental groups are respectively marked as experimental group 1-1, experimental group 1-2, experimental group 1-3, experimental group 1-4, experimental group 1-5, and experimental group 1-6. Among them, experimental group 1-1 is a basic electrolyte, serving as a control group.

[0039] Experimental group 1-1

[0040] This experimental group prepared a basic electrolyte, which included a solvent, a lithium salt and an additive.

[0041] Based on the total mass of the basic electrolyte, the solvent includes 14.90wt% ethylene carbonate (EC), 56.15wt% dimethyl carbonate (DMC) and 8.45wt% ethyl methyl carbonate (EMC). Based on the total mass of the basic electrolyte, the lithium salt includes 14.5w% lithium hexafluorophosphate (LiPF6), 0.7w% lithium bis(fluorosulfonyl)imide salt (LiFSI) and 0.8w% lithium difluorooxalatoborate (LiODFB). Based on the total mass of the basic electrolyte, the additives include 1.5wt% 1,3-propanesultone (PS) and 3wt% fluoroethylene carbonate (FEC).

[0042] Experimental Group 1-2

[0043] This experimental group prepared an electrolyte solution. The specific operation was as follows: adding a fluorescent agent to the basic electrolyte solution provided by the experimental group 1-1. The fluorescent agent was phthalimide, and the concentration of the fluorescent agent in the electrolyte solution containing the fluorescent agent was 0.1wt%.

[0044] Experimental Groups 1-3

[0045] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-2. The difference between this experimental group and experimental group 1-2 is that in the process of preparing the electrolyte, the amount of the fluorescent agent added was adjusted so that the concentration of the fluorescent agent in the electrolyte containing the fluorescent agent was 0.2wt%. The rest of the raw material ratios and preparation methods were strictly consistent with those of experimental group 1-2.

[0046] Experimental Groups 1-4

[0047] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-2. The difference between this experimental group and experimental group 1-2 is that in the process of preparing the electrolyte, the amount of the fluorescent agent added was adjusted so that the concentration of the fluorescent agent in the electrolyte containing the fluorescent agent was 0.4wt%. The rest of the raw material ratios and preparation methods were strictly consistent with those of experimental group 1-2.

[0048] Experimental Groups 1-5

[0049] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-2. The difference between this experimental group and experimental group 1-2 is that in the process of preparing the electrolyte, the amount of the fluorescent agent added was adjusted so that the concentration of the fluorescent agent in the electrolyte containing the fluorescent agent was 0.8wt%. The other raw material ratios and preparation methods were strictly consistent with those of experimental group 1-2.

[0050] Experimental Groups 1-6

[0051] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-2. The difference between this experimental group and experimental group 1-2 is that in the process of preparing the electrolyte, the amount of the fluorescent agent added was adjusted so that the concentration of the fluorescent agent in the electrolyte containing the fluorescent agent was 3.2wt%. The rest of the raw material ratios and preparation methods were strictly consistent with those of experimental group 1-2.

[0052] (2) Testing the above electrolyte

[0053] Test subjects: Electrolytes from experimental groups 1-1 to 1-6

[0054] Test method:

[0055] ① Contact angle: The contact angle of the test object on the surface of the battery cell assembly is measured using a contact angle meter. The battery cell assembly includes a positive electrode sheet, a negative electrode and a separator. The value of the contact time of 10s is used as the test result of the contact angle. Among them, the positive electrode sheet uses ternary nickel-cobalt-manganese material as the positive electrode active material, and the negative electrode uses graphite as the negative electrode active material.

[0056] The contact angle change is calculated as follows: The contact angle of the basic electrolyte of the experimental group 1-1 is taken as the reference value θ A The contact angle of the electrolyte containing the fluorescent agent is θ B , the contact angle change is θ B -θ A .

[0057] The total change in contact angle |△θ| is calculated as follows: The change in contact angle measured by the positive electrode is △θ 正 , the contact angle change measured at the negative electrode is △θ 负, the contact angle change measured by the diaphragm is △θ 隔 , the total change of contact angle |△θ|=|△θ 正 |+|△θ 负 |+|△θ 隔 |, which is the sum of the absolute values ​​of the changes in each contact angle.

[0058] The test results are shown in Table 1.

[0059] Table 1. Test results of electrolyte contact angle in Example 1

[0060]

[0061] As can be seen from the above table, as the concentration of the fluorescent agent increases, the contact angle of the electrolyte to the positive electrode sheet tends to fluctuate up and down, and the fluctuation range of the positive electrode contact angle is -2.18 to 7.99 degrees. As the concentration of the fluorescent agent increases, the contact angle of the electrolyte to the negative electrode tends to decrease first and then increase, and when the concentration of the fluorescent agent is 0.2wt%, the contact angle of the electrolyte to the negative electrode is the smallest, and the range of the contact angle of the negative electrode is -2.30 to 13.36 degrees. As the concentration of the fluorescent agent increases, the contact angle of the electrolyte to the diaphragm tends to decrease first and then increase, and when the concentration of the fluorescent agent is 0.2wt%, the contact angle of the electrolyte to the diaphragm is the smallest, and the range of the contact angle of the diaphragm is -2.86 degrees to -0.14 degrees. Therefore, it can be seen that when the concentration of the fluorescent agent in the electrolyte increases, there are differences in the changing trends of the contact angles of the electrolyte to the positive electrode sheet, the negative electrode, and the diaphragm.

[0062] In addition, the total change in contact angle △θ shown in Table 1 represents the degree of influence of the fluorescent agent concentration on the wetting characteristics of the electrolyte. As the fluorescent agent concentration increases, the total change in contact angle △θ shows an increasing trend, indicating that the greater the fluorescent agent concentration, the greater the influence on the wetting characteristics of the electrolyte.

[0063] In the process of irradiating the electrolyte provided by the above experimental groups with ultraviolet light, it was found that the lower the concentration of the fluorescent agent, the weaker the fluorescence signal intensity. When actually detecting the degree of electrolyte infiltration, the weak fluorescence signal leads to a low resolution and a large error in judging the degree of infiltration. The concentration of the fluorescent agent in the electrolyte provided by experimental groups 1-3 is 0.2wt%. The electrolyte provided by experimental groups 1-3 can not only make the electrolyte produce an obvious fluorescence effect, reducing the difficulty of detecting the fluorescence distribution, but also reduce the influence of the fluorescent agent on the infiltration characteristics of the electrolyte, thereby improving the detection accuracy of the method for detecting the degree of electrolyte infiltration.

[0064] Example 2

[0065] (1) Preparation of electrolyte

[0066] Experimental Group 2-1

[0067] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-3. The difference between this experimental group and experimental group 1-3 is that in the process of preparing the electrolyte, an equal mass of rhodamine B was used to replace the fluorescent agent in experimental group 1-3. The rest of the raw material ratio and preparation method were strictly consistent with those of experimental group 1-3, especially the concentration of the fluorescent agent was strictly consistent with that of experimental group 1-3.

[0068] Experimental group 2-2

[0069] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-3. The difference between this experimental group and experimental group 1-3 is that in the process of preparing the electrolyte, an equal mass of luminol was used to replace the fluorescent agent in experimental group 1-3. The rest of the raw material ratio and preparation method were strictly consistent with those of experimental group 1-3, especially the concentration of the fluorescent agent was strictly consistent with that of experimental group 1-3.

[0070] Experimental Group 2-3

[0071] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-3. The difference between this experimental group and experimental group 1-3 is that in the process of preparing the basic electrolyte, the fluorescent agent in experimental group 1-3 is replaced by an equal mass of rare earth material. The rest of the raw material ratio and preparation method are strictly consistent with those of experimental group 1-3.

[0072] Experimental Groups 2-4

[0073] This experimental group prepared an electrolyte with reference to the preparation method provided by experimental group 1-3. The difference between this experimental group and experimental group 1-3 is that in the process of preparing the basic electrolyte, an equal mass of fluorescein was used to replace the fluorescent agent in experimental group 1-3. The rest of the raw material ratios and preparation methods were strictly consistent with those of experimental group 1-3.

[0074] (2) Testing the above electrolyte

[0075] Test subjects: Electrolytes from experimental groups 2-1 to 2-5

[0076] Test method:

[0077] Fluorescence condition: The cylindrical battery cells were injected with the electrolytes of the above-mentioned test objects respectively, and left to stand at a temperature of 25±3℃ for 1 hour. Then, the cylindrical battery cells were disassembled in an environment with a dew point of <-40℃. Then, an ultraviolet flashlight was used to illuminate the negative electrode obtained after the disassembly of the battery cells in a dark room, and the fluorescence condition was judged by naked eye observation.

[0078] Test results: Figure 4 shown.

[0079] Comparing the fluorescence measured by experimental group 1-3 with experimental group 2-1 to experimental group 2-4, it can be found that experimental group 1-3 uses phthalimide as a fluorescent agent. After disassembling the battery, it can still clearly mark the area where the battery cell components are infiltrated by the electrolyte. However, the fluorescence measured by experimental group 2-1 to experimental group 2-4 is not as clear as the fluorescence measured by experimental group 1-3. Among them, experimental group 2-1 uses rhodamine B as a fluorescent agent. After disassembling the battery and the electrolyte volatilizing, the fluorescence is poor, and it is impossible to clearly mark the area where the battery cell components are infiltrated by the electrolyte. Experimental group 2-2 uses luminol as a fluorescent agent. After disassembling the battery, the fluorescence of the battery cell components is poor. Experimental group 2-3 uses rare earth materials as fluorescent agents. Although there are fluorescent areas in the battery cell components after disassembling the battery, the fluorescent areas are unevenly distributed and the fluorescence intensity is low. Experimental groups 2-4 used fluorescein as a fluorescent agent. After the battery was disassembled and the electrolyte volatilized, the fluorescence was poor and it was impossible to clearly mark the area of ​​the battery cell component that was infiltrated by the electrolyte.

[0080] Example 3

[0081] (1) The electrolyte infiltration degree detection method is used to determine the electrolyte infiltration degree at different standing times.

[0082] Experimental Group 3-1

[0083] This experimental group uses a method for detecting the degree of electrolyte infiltration to determine the degree of electrolyte infiltration. The method for detecting the degree of electrolyte infiltration includes the following operations:

[0084] S1. The battery cell is injected with an electrolyte containing a fluorescent agent, and allowed to stand at a temperature of 25±3°C for 1 hour. The battery cell is then disassembled in an environment with a dew point of less than -40°C. The electrolyte containing a fluorescent agent is the electrolyte provided by experimental groups 1-3, and the battery cell is a cylindrical battery cell.

[0085] S2. Use an ultraviolet flashlight to illuminate the battery cell assembly obtained by disassembling the battery cell in a dark room. The battery cell assembly includes a positive electrode, a negative electrode, and a diaphragm, and judge the degree of electrolyte infiltration based on the fluorescence distribution. The area where the battery cell assembly produces a fluorescent effect is represented by a fluorescent area, and the area where the battery cell assembly does not produce a fluorescent effect is represented by a non-fluorescent area. Use a ruler to measure the width of the non-fluorescent area of ​​the positive electrode, negative electrode, and diaphragm respectively.

[0086] The positive electrode sheet includes 97.5wt% ternary nickel-cobalt-manganese material, 0.8wt% conductive carbon black, 0.3wt% carbon nanotubes, and 1.5wt% polyvinylidene fluoride. The negative electrode includes 95.8wt% graphite, 1.2wt% conductive carbon black, 1.8wt% sodium carboxymethyl cellulose, and 1.2wt% styrene-butadiene rubber. The dimensions of the positive electrode sheet are: width 57.3mm, length 150mm, thickness 106μm; the dimensions of the negative electrode are: width 58.8mm, length 150mm, thickness 130μm.

[0087] Experimental group 3-2

[0088] This experimental group refers to the electrolyte infiltration degree detection method provided in Experimental Group 3-1 to determine the electrolyte infiltration degree. The difference between this experimental group and Experimental Group 3-1 is that: in the process of S1, it is left to stand for 10 hours. The rest of the operations are strictly consistent with Experimental Group 3-1.

[0089] Experimental group 3-3

[0090] This experimental group refers to the electrolyte infiltration degree detection method provided in Experimental Group 3-1 to determine the electrolyte infiltration degree. The difference between this experimental group and Experimental Group 3-1 is that: in the process of S1, it is left to stand for 24 hours. The rest of the operations are strictly consistent with Experimental Group 3-1.

[0091] Experimental Group 3-4

[0092] This experimental group refers to the electrolyte infiltration degree detection method provided in Experimental Group 3-1 to determine the electrolyte infiltration degree. The difference between this experimental group and Experimental Group 3-1 is that: in the process of S1, it is left to stand for 36 hours. The rest of the operations are strictly consistent with Experimental Group 3-1.

[0093] Experimental Groups 3-5

[0094] This experimental group refers to the electrolyte infiltration degree detection method provided in Experimental Group 3-1 to determine the electrolyte infiltration degree. The difference between this experimental group and Experimental Group 3-1 is that: in the process of S1, it is left to stand for 80 hours. The rest of the operations are strictly consistent with Experimental Group 3-1.

[0095] Experimental Groups 3-6

[0096] This experimental group refers to the electrolyte infiltration degree detection method provided in Experimental Group 3-1 to determine the electrolyte infiltration degree. The difference between this experimental group and Experimental Group 3-1 is that: in the process of S1, it is left to stand for 120 hours. The rest of the operations are strictly consistent with Experimental Group 3-1.

[0097] (2) The test results of the above experimental groups are shown in Table 2 and Figure 1As shown, in the process of measuring the width of the non-fluorescent area, the battery cell assembly is equally divided into a head part, a middle part, and a tail part in the length direction.

[0098] Table 2. Test results of Example 3

[0099]

[0100] Example 4

[0101] (1) The electrolyte infiltration degree detection method is used to quantitatively determine the electrolyte infiltration degree.

[0102] This embodiment adopts a method for detecting the degree of electrolyte infiltration to determine the degree of electrolyte infiltration. The method for detecting the degree of electrolyte infiltration includes the following operations:

[0103] S1. The battery cell is injected with an electrolyte containing a fluorescent agent, and is allowed to stand at a temperature of 25±3°C for 24 hours. The battery cell is then disassembled in an environment with a dew point of less than -40°C. The electrolyte containing a fluorescent agent is the electrolyte provided by experimental groups 1-3, and the battery cell is a cylindrical battery cell.

[0104] S2. Use an ultraviolet flashlight in a dark room to illuminate the battery cell assembly obtained by disassembling the battery cell, the battery cell assembly includes a positive electrode sheet, a negative electrode and a separator. Figure 2 As shown, the battery cell assembly is divided into 9 regions, namely ①②③④⑤⑥⑦⑧⑨. Specifically, the battery cell assembly is equally divided into three regions, namely the head, the middle and the tail, in the length direction, and is equally divided into three regions, namely the positive ear side (①④⑦), the middle (②⑤⑧), and the negative ear side (③⑥⑨) in the width direction, so that the battery cell assembly is divided into 9 regions; wherein, the dimensions of the positive electrode sheets in these 9 regions are: width 19.1mm, length 50mm, thickness 106μm. The dimensions of the negative electrode in these 9 regions are: width 19.6mm, length 50mm, thickness 130μm. The fluorescence intensity of the 9 regions is tested respectively, and the fluorescence intensity of the 9 regions is normalized to quantitatively characterize the degree of electrolyte infiltration in the battery cell assembly.

[0105] The positive electrode sheet includes 97.5wt% ternary nickel-cobalt-manganese material, 0.8wt% conductive carbon black, 0.3wt% carbon nanotubes, and 1.5wt% polyvinylidene fluoride. The negative electrode includes 95.8wt% graphite, 1.2wt% conductive carbon black, 1.8wt% sodium carboxymethyl cellulose, and 1.2wt% styrene-butadiene rubber.

[0106] The test results are shown in Table 3.

[0107] Table 3. Normalized fluorescence intensity characterization results of positive electrode, negative electrode and separator

[0108]

[0109]

[0110] Note: The battery cell assembly is divided into three areas in the length direction, named as the head, middle and tail respectively; the battery cell assembly is divided into three areas in the width direction, named as the positive ear side, middle and negative ear side respectively.

[0111] Example 5

[0112] (1) This embodiment optimizes the design of lithium-ion batteries by adopting the above-mentioned method for detecting the degree of electrolyte infiltration.

[0113] Experimental Group 5-1A

[0114] This experimental group refers to the electrolyte infiltration degree detection method provided in Example 4 to determine the electrolyte infiltration degree. The difference between this experimental group and Example 4 is that in the process of S1, the injection process and the standing time are adjusted. The specific operation includes taking vacuum -85kpa ​​and positive pressure 0.2Mpa as one cycle. The number of cycles in this experimental group is 2 times. After the injection is completed, it is left standing at a temperature of 25±3℃ for 24 hours. The rest of the operations are strictly consistent with Example 4.

[0115] Experimental Group 5-2A

[0116] This experimental group refers to the electrolyte infiltration degree detection method provided by experimental group 5-1A to determine the electrolyte infiltration degree. The difference between this experimental group and experimental group 5-1A is that in the process of S1, the liquid injection process is adjusted. The specific operation includes vacuum -85kpa ​​and positive pressure 0.3Mpa as one cycle, and the number of cycles in this experimental group is 4 times. The rest of the operations are strictly consistent with experimental group 5-1A.

[0117] Experimental Group 5-3A

[0118] This experimental group refers to the electrolyte infiltration degree detection method provided by experimental group 5-1A to determine the electrolyte infiltration degree. The difference between this experimental group and experimental group 5-1A is that in the process of S1, the injection process and the standing time are adjusted. The specific operation includes vacuum -85kpa ​​and positive pressure 0.3Mpa as one cycle. The number of cycles in this experimental group is 6 times. After the injection is completed, it is left to stand at a temperature of 45℃ for 24 hours. The rest of the operations are strictly consistent with experimental group 5-1A.

[0119] Experimental Group 5-1B

[0120] This experimental group prepared a battery with reference to the battery preparation method provided by experimental group 5-1A. The difference between this experimental group and experimental group 5-1A is that the operation of adding fluorescent agent to the basic electrolyte is omitted. The rest of the operations are strictly consistent with experimental group 5-1A, that is, the battery adopts the injection process and standing time of experimental group 5-1A.

[0121] Specifically, the battery includes an electrolyte, a positive electrode, a negative electrode, and a separator. The electrolyte uses the basic electrolyte provided by the experimental group 1-1, and the positive electrode includes 97.5wt% of ternary nickel-cobalt-manganese material, 0.8wt% of conductive carbon black, 0.3wt% of carbon nanotubes, and 1.5wt% of polyvinylidene fluoride. The negative electrode includes 95.8wt% of graphite, 1.2wt% of conductive carbon black, 1.8wt% of sodium carboxymethyl cellulose, and 1.2wt% of styrene-butadiene rubber.

[0122] Experimental Group 5-2B

[0123] This experimental group prepared a battery with reference to the battery preparation method provided by experimental group 5-2A. The difference between this experimental group and experimental group 5-2A is that the operation of adding fluorescent agent to the basic electrolyte is omitted. The rest of the operations are strictly consistent with experimental group 5-2A, that is, the battery adopts the injection process and standing time of experimental group 5-2A.

[0124] Experimental Group 5-3B

[0125] This experimental group prepared a battery with reference to the battery preparation method provided by experimental group 5-3A. The difference between this experimental group and experimental group 5-3A is that the operation of adding fluorescent agent to the basic electrolyte is omitted. The rest of the operations are strictly consistent with those of experimental group 5-3A, that is, the battery adopts the injection process and standing time of experimental group 5-3A.

[0126] The fluorescence intensity characterization results of experimental groups 5-1A to 5-3A are shown in Table 4.

[0127] Table 4. Normalized characterization results of fluorescence intensity of experimental groups 5-1A to 5-3A

[0128]

[0129]

[0130] Note: The fluorescence intensity of the positive electrode side of the experimental group 5-1A was used as the reference for normalization.

[0131] (2) Test the batteries provided by Experimental Groups 5-1A to 5-3A and Experimental Groups 5-1B to 5-3B

[0132] Test method: Perform 1C-3C (charging rate is 1C, discharging rate is 8C) cycle performance test on the batteries provided by experimental group 5-1A ~ experimental group 5-3A, experimental group 5-1B ~ experimental group 5-3B, the number of cycles is 500, and the capacity retention rate is recorded. The capacity retention rate measured by experimental group 5-1B ~ experimental group 5-3B is as follows Figure 3 shown.

[0133] From the fluorescence intensity shown in Table 5, it can be seen that in the battery provided by the experimental group 5-1A, the fluorescence intensity of the middle region is about 50% of that of the positive electrode side region. In the battery provided by the experimental group 5-2A, the fluorescence intensity of the middle region is about 70% of that of the positive electrode side region. In the battery provided by the experimental group 5-3A, the fluorescence intensity of the middle region is about 90% of that of the positive electrode side region, and the fluorescence intensity of the middle region is close to that of the negative electrode side.

[0134] like Figure 3 As shown, the cycle capacity retention rate of the battery provided by the experimental group 5-1B is 53.96%, the cycle capacity retention rate of the battery provided by the experimental group 5-2B is 79.26%, and the cycle capacity retention rate of the battery provided by the experimental group 5-3B is 86.9%.

[0135] In summary, the electrolyte wetting degree measured by Experimental Group 5-1A to Experimental Group 5-3A is consistent with the change trend of the cycle capacity retention rate measured by the batteries provided by Experimental Group 5-1B to Experimental Group 5-3B. In other words, the detection method of the electrolyte wetting degree can effectively detect the electrolyte wetting degree, thereby optimizing the design of lithium-ion batteries.

[0136] In addition, in the process of testing the cycle capacity retention rate, it was found that when adjusting the parameters of the formation process, such as adjusting the formation voltage, as the formation voltage increases, the change pattern of the cycle capacity retention rate presented by the batteries provided by the experimental groups 5-1B to 5-3B and the batteries provided by the experimental groups 5-1A to 5-3A is not exactly the same. In other words, the introduction of fluorescent agents in the formation stage will affect the electrochemical performance of the battery, thereby affecting the detection accuracy, and it is difficult to accurately detect the parameter adjustment of the formation stage with the electrolyte containing fluorescent agents.

[0137] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for detecting the degree of electrolyte infiltration, characterized in that: The following operations are included: S1. Injecting the battery cell with an electrolyte containing a fluorescent agent, allowing it to stand, and then disassembling the battery cell; S2. Use ultraviolet light to irradiate the battery cell assembly obtained by disassembling the battery cell, wherein the battery cell assembly includes at least one of a positive electrode sheet, a negative electrode, and a separator, and determine the degree of infiltration of the electrolyte according to the fluorescence distribution.

2. The method for detecting the electrolyte infiltration degree according to claim 1, characterized in that: The fluorescent agent includes a phthalimide-type fluorescent agent.

3. The method for detecting the electrolyte infiltration degree according to claim 1, characterized in that: The concentration of the fluorescent agent in the electrolyte is 0.1-3.2 wt %.

4. The method for detecting the electrolyte infiltration degree according to claim 3, characterized in that: The concentration of the fluorescent agent in the electrolyte is 0.2 wt %.

5. The method for detecting the electrolyte infiltration degree according to claim 1, characterized in that: The electrolyte includes at least one of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate.

6. The method for detecting the electrolyte infiltration degree according to claim 5, characterized in that: The electrolyte includes dimethyl carbonate.

7. The method for detecting electrolyte infiltration degree according to claim 1, characterized in that: The electrolyte further comprises at least one of lithium hexafluorophosphate, bis(fluorosulfonyl)imide lithium salt, lithium difluorooxalatoborate, 1,3-propanesultone, and fluoroethylene carbonate.

8. The method for detecting the electrolyte infiltration degree according to any one of claims 1 to 7, characterized in that: The battery cell is a cylindrical battery cell, and the area of ​​the battery cell component that does not produce a fluorescent effect is represented by a non-fluorescent area; When determining the infiltration degree of the electrolyte, the infiltration degree of the electrolyte in the battery cell assembly is determined based on the width of the non-fluorescent area.

9. The method for detecting the electrolyte infiltration degree according to any one of claims 1 to 7, characterized in that: When judging the degree of infiltration of the electrolyte, the following operations are included: Divide the battery cell assembly into M parts in the length direction and divide the battery cell assembly into N parts in the width direction, so that the battery cell assembly is divided into M*N areas, where M≥2 and N≥2; The fluorescence intensities of the M*N regions are tested respectively, and the fluorescence intensities of the M*N regions are normalized to quantitatively characterize the degree of infiltration of the electrolyte in the battery core assembly.

10. Use of the method for detecting electrolyte wetting degree according to any one of claims 1 to 9 in optimizing lithium ion battery design.

Citation Information

Patent Citations

  • Method for predetermining electrolyte distribution of lithium ion power battery and battery preparation method

    CN108565496A

  • Test method for consistency of battery electrolyte infiltration

    CN110160915A

  • Characterization method for wettability of electrolytic solution

    CN113237792A

  • Visual testing method for infiltration condition of porous electrode

    CN115326642A

  • Method for quantitatively analyzing infiltration condition of electrolyte in battery cell

    CN118549294A

Cited By

  • Method for measuring infiltration degree of electrolyte of battery cell

    CN121977974A